Pengaruh Kondisi Ekonomi Keluarga dan Motivasi Belajar terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Kewirausahaan Kelas XII di SMK Teknomedika 2 Cibungbulang Bogor - Yati Nurhidayati; Nanat Fatah Natsir; Efrita Norman (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
This research is motivated by the Family Economic Conditions, Learning Motivation, and Student Learning Achievement. The purpose of this study was to analyze the influence of Family Economic Conditions and Learning Motivation Against Student Learning Achievement in Entrepreneurship Class XII in SMK Teknomedika 2 Cibungbulang Bogor. This research was conducted using a sample of 42 students, using a random sampling technique from a population of 140 students. Consists of independent variable the Family Economic Conditions (X1), Learning Motivation (X2) and dependent variable Student Learning Achievement (Y). Researchers use quantitative data analysis, the stage of implementation of the analysis includes: (1) descriptive analysis, (2) classical assumption test (prerequisite) and (3) hypothesis testing. The results of this study indicate that: 1) There is a significant influence on the family economy of student achievement in SMK Teknomedika 2 Cibungbulang Bogor by 50.7%. 2) There is a significant influence of learning motivation on student achievement in SMK Teknomedika 2 Cibungbulang Bogor by 51.0%. 3) There is a significant influence between family economy and learning motivation together on student achievement in SMK Teknomedika 2 Cibungbulang Bogor by 69.7% while the remaining 30.3% is influenced by other variables not examined in this study . Keywords: family economy, learning motivation, and learning achievement.